IMPROVING STUDENTS’ ACHIEVEMENT IN READING COMPREHENSION THROUGH THINK PAIR SHARE TECHNIQUE - Fenny Friska Sormin; Siti Aisah Ginting (Universitas Negeri Medan, 2012)
ABSTRACT This study deals with improvement students’ achievement in reading comprehension through Think Pair Share Technique (TPS). This study was conducted by using classroom action research. The subject of the research was class X-B SMA Parulian 2 Medan which consists of 38 students. The research was conducted in two cycles and each cycle consists of three meetings. The instrument for collecting data were quantitative data (reading comprehension test) and qualitative data (diary notes, observation sheets, and interview sheet). Based on reading comprehension score, students’ score kept improving in every test. In orientation test the mean score was 62.50, in cycle I the mean of writing score was 70.52, in cycle II the mean of reading comprehension score was 80.13. Based on diary notes, observation sheets and interview sheet, it was found that teaching learning process ran well. Students were active and interested in reading comprehension. The result of the research showed that Think Pair Share Technique (TPS) can improve students’ achievement in reading comprehension. Key Words: Reading Comprehension, Think Pair Share Technique(TPS)